Relationship between academic self-efficacy, performance and anxious and depressive symptoms in emerging adult college students - Gutiérrez García, Ana (2020)
The objective of the present investigation was to explore the levels of academic self-efficacy and their relationship with performance, anxiety and depression in a sample of emerging university adults. 114 students between 17 and 30 years of age (SD = 2.12), answered the in the Academic Behavior Self-efficacy Scale, the Diagnostic Questionnaire for Depressive Disorders and an Anxiety Inventory. For academic performance, the average grade for high school education, the university entrance exam and the first semester of university were considered. The analysis of the measurement of the levels of each of these variables and their correlation, indicated that the respondents who had low academic self-efficacy when entering university, had the lowest academic performance during high school and a high level of anxiety upon entering university without symptoms of depression.